PENGARUH KETINGGIAN TERBANG TERHADAP ENDURANCE MAKSIMUM TERBANG JELAJAH PESAWAT N219 MENGGUNAKAN METODE Pr-V - Akhmad Nirman Zaki; Hary Sutjahjono; FX. Kristianta (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
As a plane that is still in flight testing period then the N219 aircraft needs to be assessed for evaluation purposes. Focus in this study is on field of performance. This field is studied to determine the performance of N219 aircraft especially in the cruise phase. This study was conducted with the aim to determine the effect of variations in the selection of flying alititudes on the achievement of maximum endurance flying. The calculation method is done by using Pr-V graph. This method is used to determine the maximum endurance through the minimum power required curve. The result show that the increase in flying height cause the decrease of air density. This happens because the pressure and temperature of the air also decreases with increasing height. In addition, the increase in flying altitude also affects the fuel flow. Fuel flow decrease with increasing altitude. Conversely, the maximum endurance increases with the increase in altitude. This happens because the endurance is derived from the division of the fuel flow weight, so the endurance is inversely proportional to the fuel flow. The lowest maximum endurance value occurs at sea level is 6,48 jam, and the highest maximum endurance value occurs at 10.000 ft is 8,65 jam. Keywords: Endurance, cruise, altitude